The transition from children's services to adult services for young people with attention deficit hyperactivity disorder: the CATCh-uS mixed-methods study - Astrid Janssens; Helen Eke; Anna Price; Tamsin Newlove-Delgado; Sharon Blake; Cornelius Ani; Philip Asherson; Bryony Beresford; Tobit Emmens; Chris Hollis; Stuart Logan; Moli Paul; et al. (National Institute for Health Research, 2020)
Background: Attention deficit hyperactivity disorder was previously seen as a childhood developmental disorder, so adult mental health services were not set up to support attention deficit hyperactivity disorder patients who became too old for child services. To our knowledge, this is the first in-depth study of the transition of attention deficit hyperactivity disorder patients from child to adult health services in the UK. Objectives: Our objectives were to explore how many young people with attention deficit hyperactivity disorder are in need of services as an adult, what adult attention deficit hyperactivity disorder services are available and how attention deficit hyperactivity disorder stakeholders experience transition from child to adult services. Design: An interactive mixed-method design was adopted with three study streams: (1) a 12-month surveillance study with 9-month follow-up to find out how many young people required ongoing medication when they were too old for child services (929 surveys completed by children's clinicians); (2) a mapping study to identify and describe services for young adults with attention deficit hyperactivity disorder (2686 respondents to online surveys for patients and health workers and freedom of information requests to service providers and commissioners); and (3) a qualitative study to explore key stakeholders' experiences of transition from child to adult services (144 interviews with 64 attention deficit hyperactivity disorder patients, 28 parents and 52 health clinicians; 38 working in child or adult secondary health services and 14 general practitioners). Members of the public advised at each stage of the study. Results: When corrected for non-response and case ascertainment, the annual number of young people with an ongoing need for medication for attention deficit hyperactivity disorder lies between 270 and 599 per 100,000 people aged 17-19 years. Among 315 individuals eligible for transition, 64% were accepted, but only 22% attended their first adult services appointment. Our interactive map describes 294 unique services for adults with attention deficit hyperactivity disorder across the UK, of which 44 are 'dedicated' attention deficit hyperactivity disorder services. Few services provide the full range of recommended provision; most focus on diagnosis and medication. Services are unevenly distributed across the UK, with nearly all 'dedicated' services being in England. Exploring stakeholders' experiences revealed how invested the stakeholders are in continuing attention deficit hyperactivity disorder treatment and how the architecture of services affects transition. An association between attention deficit hyperactivity disorder, education and continuance of medication into young adulthood, plus parent involvement and feeling prepared for transition and adult life with attention deficit hyperactivity disorder, influenced investment. However, even with investment, how accessible adult services are, how patient needs fit with the remit of the adult service and the level of patient information available affect transition outcomes. The results also highlight how general practitioners can end up as care co-ordinators during transition by default. Limitations: Transition estimates were based on those who want medication, so these indicate a minimum level of need. Conclusions: Few of those who need ongoing support for attention deficit hyperactivity disorder successfully transfer to adult services, and a small proportion of those who transfer experience optimal transitional care. Adult attention deficit hyperactivity disorder service provision is patchy. Even among 'dedicated' services, few provide the whole range of National Institute for Health and Care Excellence-recommended treatments. Future work: We need to evaluate various models of transitional care and adult attention deficit hyperactivity disorder provision, as well as develop and evaluate psychosocial interventions for young people and adults with attention deficit hyperactivity disorder. Trial registration: Current Controlled Trials ISRCTN12492022. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Services and Delivery Research programme and will be published in full in Health Services and Delivery Research; Vol. 8, No. 42. See the NIHR Journals Library website for further project information.